A Variant of t-PA (T103N, KHRR 296-299 AAAA) that, by Bolus, Has Increased Potency and Decreased Systemic Activation of Plasminogen - Refino, Canio J; Paoni, Nicholas F; Keyt, Bruce A; Pater, Cheryl S; Badillo, Julie M; Wurm, Florian M; Ogez, John; Bennett, William F (Thrombosis and Haemostasis, 1993)
In the accompanying paper, we reported that the properties of decreased plasma clearance rate, increased fibrin specificity, and resistance to inactivation by PAI-1 could be effectively combined in the t-PA variant T103N, KHRR 296-299 AAAA. In the current study we evaluated the in vivo efficacy of this variant as well as variants containing the individual mutations T103N and KHRR 296-299 AAAA. Plasma clearance and in vivo lysis of whole blood and platelet-rich clots were determined in a rabbit arterio-venous shunt model. The T103N containing variants were administered as an intravenous (i.v.) bolus. KHRR 296-299 AAAA and t-PA were infused i.v. over 90 min. The clearance rate of the KHRR 296-299 AAAA variant was similar to t-PA. However, the clearance of the T103N and T103N, KHRR 296-299 AAAA variants were 8 and 6-fold reduced, respectively. Potency of the variants relative to t-PA on whole blood clots ranged from 0.9 (T103N, KHRR 296-299 AAAA) to 1.7 (T103N). Relative potency on platelet-rich clots ranged from 2.4 (T103N) to 4.2 (T103N, KHRR 296-299 AAAA). Fibrinogen concentrations in rabbits 120 min after dosing with a 2.5 mg/kg bolus were: 24, 16, 82, and 77% of initial for t-PA; T103N; KHRR 296-299 AAAA; and T103N, KHRR 296-299 AAAA treatment groups, respectively. These results suggest that the T103N, KHRR 296-299 AAAA variant of t-PA, given as a bolus, could result in greater efficacy, particularly on refractory platelet-rich clots, without inducing the severe systemic lytic state produced by a bolus of a less fibrin specific variant.